Bio and magnetostratigraphy of two Lower Miocene sections, Tagus basin (Portugal) - Sen, S. (1992)
The magnetostratigraphy of two sections in early Miocene marine deposits of the Tagus Basin is studied. Thermal demagnetization was used to isolate the primary component of magnetization for 45 samples from the Foz da Fonte section, and for 74 others from Trafaria section. The succession of the polarity zones found in these sections is tentatively correlated with the geomagnetic polarity time scale (GPTS) on the basis of the biostratigraphic data yielded by planktic Foraminifera. The planktic zones and magnetic polarities recognized in these sections can be adequately correlated with the part of the GPTS [table calibrated by BERGGRENET al. (1985)] corresponding to the Anomalies 6 and 5E (Foz da Fonte) and 5D (Trafaria). This correlations suggests ages between 19,35 and 18,14 Ma for Foz da Fonte section, and 17,90 to 16,98 Ma for Trafaria.